If on a winter's night a traveler - Calvino, Italo; Weaver, William 1923-2013 (New York Knopf Distributed by Random House, 1993)
Based on a analogy between the reader's desire to finish the story and the lover's desire to consummate his or her passion, this book is the tale of two bemused readers whose attempts to reach the end of the same book are constantly and comically frustrate.
If on a winter's night a traveler -- Outside the town of Malbork -- Leaning from the steep slope -- Without fear of wind or vertigo -- Looks down in the gathering shadow -- In a network of lines that enlace -- In a network of lines that intersect -- On the carpet of leaves illuminated by the moon -- Around an empty grave -- What story down there awaits its end?
Includes bibliographical references (p. xxvi-xxvii).
KAL-3215, Mr. Gary Colmenar.
Keywords: Italian fiction